Identification of a Chlorophyll Dephytylase Involved in Chlorophyll Turnover in Arabidopsis. Issue 12 (5th December 2016) - Lin, Yao-Pin; Wu, Meng-Chen; Charng, Yee-yung
Abstract : Characterization of an Arabidopsis heat-sensitive mutant identified a chlorophyll dephytylase involved in steady-state chlorophyll turnover, revealing a pathway of chlorophyll metabolism. Abstract: Chlorophyll turns over in green organs during photosystem repair and is salvaged via de- and rephytylation, but the enzyme involved in dephytylation is unknown. We have identified an Arabidopsis thaliana thylakoid protein with a putative hydrolase domain that can dephytylate chlorophyll in vitro and in vivo. The corresponding locus, CHLOROPHYLL DEPHYTYLASE1 ( CLD1 ), was identified by mapping a semidominant, heat-sensitive, missense allele ( cld1-1 ). CLD1 is conserved in oxygenic photosynthetic organisms, sharing structural similarity with pheophytinase, which functions in chlorophyll breakdown during leaf senescence. Unlike pheophytinase, CLD1 is predominantly expressed in green organs and can dephytylate chlorophyll in vitro. The specific activity is significantly higher for the mutant protein encoded by cld1-1 than the wild-type enzyme, consistent with the semidominant nature of the cld1-1 mutation. Supraoptimal CLD1 activities in cld1-1 mutants and transgenic seedlings led to the proportional accumulation of chlorophyllides derived from chlorophyll dephytylation after heat shock, which resulted in light-dependent cotyledon bleaching. Reducing CLD1 expression diminished thermotolerance and the photochemical efficiency of photosystem II under prolonged moderate heat stress. Taken together, our results suggest that CLD1 is the long-sought enzyme for removing the phytol chain from chlorophyll during its turnover at steady state within the chloroplast.